Studies on the Forms of Potassium and Potassium Fixing Capacity in Some Arid Soils of Jodhpur Region - Joshi, D C; Johri, S N; Sharma, V C (Annals of Arid Zone, 2016)
Studies on the forms of potassium and potassium fixing capacity have been carried out in nine profiles of arid region. HCI soluble, water soluble and exchangeable potassiam were low and N HNO3 soluble and fixed potassium were in comparable amounts with that in semi-arid and sub-humid soils. Significant correlation of organic carbon, CaCO3, clay contents and CEC of soils with forms and fixing capacity of soils indicated their impact on relative accumulation of different forms of potassium and their distribution in profiles. Potassium fixing capacity of arid soils ranged from 0.3 to 1.9 m. eq./1OO gm soils. Low fixing capacity was related with the higher potassium saturation of these soils.